Analisis Jual Beli Objek Hak Tanggungan Yang Dilakukan Di Bawah Tangan Menurut Peraturan Perundang-Undangan Di Indonesia - Annisa Rahma Rafidah (Zhata Institut, 2024)
The sale of mortgage objects under private agreement can be carried out based on an agreement between the debtor and creditor, in addition to public auction as a means of enforcement. In the Mortgage Law, specifically Article 20 paragraphs (2) and (3), it is stipulated that this mechanism is an alternative means of settling the debtor's obligations. This study aims to identify the obstacles that arise in the practice of selling mortgage objects under the table and to find solutions to improve the effectiveness of its implementation. The method used is normative legal research with a regulatory approach. Mortgage rights themselves are a type of collateral that grants priority status to certain creditors over others. From the research conducted, it can be concluded that the private sale mechanism demonstrates higher effectiveness. However, the implementation of the sale of mortgage objects faces significant obstacles, including the reluctance of debtors to vacate properties that are still occupied and the mismatch between the seller's expectation of a high price to cover all obligations and the buyer's desire for a fair price in line with market conditions. To address these challenges, strategies for resolving problematic loans in the banking sector are implemented through a consultative approach with debtors to reach a consensus on conducting under-the-table sales.